Reliability, validity and distribution of the Spanish female sexual function index in women with relapsing multiple sclerosis - Sara Gil-Perotin; Salma Reddam; Cristina González-Mingot; Anna Gil-Sánchez; Inés González-Suarez; Silvia Peralta; Patricia Escrivá; Lucas Barea-Moya; Beatriz Sánchez-Sánchez (BMC, 2023)
Abstract Background The Female Sexual Function Index (FSFI) is a widely recognized tool for assessing sexual dysfunction (SD). However, its validation for Spanish women suffering from multiple sclerosis (MS) has not yet been conducted. Aim The study aimed to examine the psychometric properties of the 19-item Spanish version of the FSFI (svFSFI) in women with relapsing MS. Method A total of 137 women with relapsing MS from three Spanish centers participated in the study and completed the svFSFI. The psychometric properties of the questionnaire were evaluated. The prevalence of SD in the study cohort was determined, and its association with clinical and sociodemographic variables was analyzed using bi- and multivariate regression analyses. Results The svFSFI demonstrated excellent test-retest reliability and substantial-to-excellent internal consistency in the context of relapsing MS. There was significant convergent validity in the intercorrelations of domains. Discriminant validity showed differences in SD between women with high and low neurological disability, as measured by the Expanded Disability Status Scale (EDSS) scores. An exploratory factor analysis indicated a five-factor structure for the svFSFI. The prevalence of SD in the MS cohort was found to be 42.6%, with the 'desire' and 'arousal' domains being the most affected. Factors such as EDSS score, fatigue, depression, and having a stable partner were found to influence the total svFSFI score. Conclusion The study validates the svFSFI as a reliable and valid instrument for evaluating sexual dysfunction in Spanish women with MS.